Обґрунтування конструктивних параметрів скреперно-роликового пристрою для прибирання гною - Ікальчик, М. І.; Ikalchyk, Mykola (КНТУ, 2015)
В даній статті розглянуті недоліки існуючих скреперних установок для видалення гною. Розроблений скреперно-роликовий пристрій для прибирання гною в якому на краях скребків закріплено по ролику, які будуть не ковзати, а перекочуватись по стінці гнойового каналу, що забезпечить зменшення енерговитрат при прибиранні гною. В результаті проведення експериментальних досліджень та обробки їх результатів побудовані поверхні відгуків і їх двомірні перетини та визначені значення факторів, при яких споживана потужність приймає мінімальне значення. The article is devoted to the problem of reducing energy consumption for manure in the Loose boxed hold cattle through improved design scrapers installation. An patent information retrieval, analyzed scientific works and other sources of information concerning the process of manure scraper settings. Considered shortcomings of existing installations winches to remove manure. Based on the results of research and systems analysis presents recommendations for designing the scraper unit. Designed scraper roller device in which manure scrapers on the edges in video fix that will not slide, and rolled on the wall manure channel that will reduce energy consumption in the manure. As a result of experimental research and processing of results built surface of reviews and their two-dimensional section and identified the factors mentioned in which power consumption takes a minimum value.
Justification design parameters-roller scraper device for manure
Keywords: скреперна установка; гній; кут розкриття; ролик; енерговитрати; scraper installation; manure; opening angle; roller; energy consumption